THE INFLUENCE OF PROMOTION AND APPLICATION FEATURES ON INCREASING ONLINE TRANSACTIONS OF LIVIN MERCHANT APPLICATION USERS WITH USER SATISFACTION AS AN INTERVENING VARIABLE (CASE STUDY AT BANK MANDIRI KC MEDAN IMAM BONJOL) - Febrina Sari Nst (Universitas Efarina, 2025)
This study aims to analyze the influence of promotions and application features on user satisfaction and their impact on increasing online transactions. The research method uses a quantitative approach with Partial Least Squares (PLS-SEM) analysis techniques. The results show that promotions have a significant effect on user satisfaction and increasing online transactions. Meanwhile, application features do not have a direct effect on increasing online transactions, but have a significant effect on user satisfaction. Furthermore, user satisfaction is proven to have a significant effect on increasing online transactions, while also acting as a mediator that strengthens the influence of application features on online transactions. However, user satisfaction does not mediate the effect of promotions on increasing online transactions. This finding confirms that promotions are more effective in directly encouraging transactions, while application features play a greater role in building satisfaction that impacts transaction sustainability.